On Old World ninetine spiders (Araneae: Pholcidae), with a new genus and species and the first record for Madagascar - Huber, Bernhard A.; El-Hennawy, Hisham K. (Zootaxa, 2007)
Ninetines (Pholcidae: Ninetinae) are tiny spiders, largely restricted to arid habitats where they lead reclusive lives under objects close to the soil. They are rare in collections and poorly known in any respect. Only two genera were previously known from the Old World, the monotypic Mystes Bristowe from Malaysia, and Ninetis Simon, with four described species ranging from Yemen to Namibia. Here we describe a new genus from Egypt and Uzbekistan, represented by a single new species, Nita elsaff n. gen., n. sp. Based on ultrastructural data and cladistic analysis we hypothesize that this species is more closely related to some largely New World ninetines (Chisosa Huber from Baja California and Texas, Aucana Huber from Chile and New Caledonia) than to Ninetis. We also describe the first Ninetis species from Madagascar (N. toliara n. sp.), give new records for two previously known species, and present a distribution map for Ninetis.